2016
DOI: 10.1136/tobaccocontrol-2016-053114
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Spanish smoking legislations in the adoption of smoke-free rules at home: a longitudinal study in Barcelona (Spain)

Abstract: The implementation of the smoke-free regulations in public and work places in Spain was associated with an increasing of voluntary adoption of smoke-free rules in homes. According to our data, the Spanish smoking bans did not shift the tobacco consumption from public and work places to private places (homes).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…Regidor et al 32 found evidence of an initial equity-positive effect on the population quit ratio followed by a longer-term drift towards equity-negative impacts (among males). Lidón-Moyano et al 43 reported a possible equity-negative effect of the same legislation on the voluntary adoption of smoke-free homes. Evaluation of similar smoke-free legislation in Luxembourg 48 found inconsistent and inconclusive results for smoking prevalence but clearer evidence of an equity-positive effect for quitting as a result of the ban.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regidor et al 32 found evidence of an initial equity-positive effect on the population quit ratio followed by a longer-term drift towards equity-negative impacts (among males). Lidón-Moyano et al 43 reported a possible equity-negative effect of the same legislation on the voluntary adoption of smoke-free homes. Evaluation of similar smoke-free legislation in Luxembourg 48 found inconsistent and inconclusive results for smoking prevalence but clearer evidence of an equity-positive effect for quitting as a result of the ban.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 19 664 were excluded following initial title/abstract screening. A further 114 were judged ineligible through the detailed abstract review and 52 through the full-text review, with most excluded because they focused on young people not adults (43), because the policy was unclear or not evaluated (31), or because the study examined cessation support but did not assess population reach (27). The remaining 64 references were combined with 4 identified through hand-searching to give 68 papers for inclusion.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Moreover, another longitudinal study, showed a significant decrease in the prevalence of selfdeclared SHS exposure at workplaces, during leisure time, at home, and public transport after the application of the two Spanish smoking legislations 25 . Other studies, carried out in Spain using questionnaire, showed a decrease in self-declared SHS exposure in all the studied settings after the application of the smoking legislations 16,26,27 . Similar results can be found in Ireland 28 , Scotland 29 , Italy 30 , and USA 31 .…”
Section: Discussionmentioning
confidence: 61%
“…The main limitation of our study is the potential participation bias due to the attrition of the cohort of participants. In this sense, there were statistically significant differences according to age, level of education, and smoking status between the follow-up sample and the participant lost in both stages of the follow-up 27 . Follow-up participants overestimate the young people and smokers in comparison with lost participants.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation